Is a university committed to ethics perceived as an honest, appropriate and properly managed organization? - Delgado-Alemany, Rafael; Revilla-Camacho, Maria Angeles; Blanco-González, Alicia (Journal of Management and Business Education, 2020)
Universities, as organizations that must compete to attract resources, faculty, and students, also strive to implement quality policies and ethical standards. This attempt to improve also involves the management of intangible assets, which to date were not considered by this type of organization (reputation, image and legitimacy). With the aim of validating whether the universities with ethical codes and deontology subjects in their study plans are also positively perceived by students and professors, we carried out an empirical study at the Rey Juan Carlos University. The results provide valuable information for decision-making and communication of the actions carried out by the university, highlighting that a greater effort is necessary so that the effort of a university to consider itself ethical translates into its positive perception in its groups of close interest.